An Account of an extensive collection of archaeological relics, and osteological remains, from a 'Pict's House,' at Kettleburn, Caithness (Proceedings of the Society of Antiquaries of Scotland, 1855)
Details of an excavation and findings of the "Pict's House" at Kettleburn. Alexander Henry Rhind notes where artefacts similar to those found during this excavation were found and also speculates on their uses.